2009
DOI: 10.1242/jcs.019117
|View full text |Cite
|
Sign up to set email alerts
|

Integrins in immunity

Abstract: A successful immune response depends on the capacity of immune cells to travel from one location in the body to another–these cells are rapid migrators, travelling at speeds of μm/minute. Their ability to penetrate into tissues and to make contacts with other cells depends chiefly on the β2 integrin known as LFA-1. For this reason, we describe the control of its activity in some detail. For the non-immunologist, the fine details of an immune response often seem difficult to fathom. However, the behaviour of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
261
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(275 citation statements)
references
References 131 publications
4
261
0
3
Order By: Relevance
“…Integrins are special molecules that have outside-in and inside-out pathways mediated by their conformational changes (bent: inactive; extended: intermediate affinity; extended with open conformation: high affinity) (13,14). CD11b is widely expressed in DCs, NK cells, macrophages, and activated CTLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrins are special molecules that have outside-in and inside-out pathways mediated by their conformational changes (bent: inactive; extended: intermediate affinity; extended with open conformation: high affinity) (13,14). CD11b is widely expressed in DCs, NK cells, macrophages, and activated CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…According to their distinct a subunits, they are divided into four functional heterodimers termed LFA-1 (CD11a/CD18, aLb2 integrin, ITAL Ag), Mac-1 (CD11b/CD18, aMb2 integrin, ITAM Ag), p150,95 (CD11c/CD18, aXb2 integrin, CR4, ITAX Ag), and aDb2 (CD11d/CD18, ITAD Ag). CD11b is extensively expressed in most immune cells, such as DCs, monocytes/macrophages, granulocytes, and NK cells, and it participates in cell activation, chemotaxis, cytotoxicity, and phagocytosis (13,14). Our previous reports showed that CD11b is able to maintain immunological tolerance and inhibit inflammatory responses by repressing TLR3 signaling in NK cells and TLR4 signaling in macrophages (15,16).…”
mentioning
confidence: 99%
“…1), bind to a diverse collection of ligands which are mostly large molecules, usually found in the subendothelial matrix, including fibronectin 1 , vitronectin 9 and collagen 10 . Other ligands are plasma proteins including complement factors 11 , C-reactive protein 12 and fibrinogen 13 . Many integrins also recognize the amino acid sequence Arg-Gly-Asp (RGD) in their ligands 2,14 .…”
Section: Physiological Role Of Integrinsmentioning
confidence: 99%
“…Integrins have a key role in the migration and interaction of cells of the immune system. Both β 1 and β 2 integrins are important in immune function where they play essential roles in localizing the immune response to the site of inflammation 11 and a defect in β 2 integrins leads to life-threatening immune dysfunction (leucocyte adhesion deficiency, LAD) 32 . Engagement of the T-cell receptor and subsequent inside-out signalling leads to activation of T-cell integrins 18 .…”
Section: Integrins and Diseasementioning
confidence: 99%
See 1 more Smart Citation